An experience of Social group work with patients with serious and chronic mental illness. An alternative of psychosocial recovery - Alonso, Cristina (Cuadernos de Trabajo Social, 2014)
This article tries to show a way of group intervention, under the regard of a social worker. Participants are people with chronic and severe mental illness, all of them included in a program of psychosocial rehabilitation and therapeutic monitoring, known as continuity of care. The protagonists show stories and personal testimonies in their way of living and feeling mental illness. A group intervention which rescues difficulties in social relationships and professional look focuses on enhancing expressive capabilities as well as on sharing resources in group to address them. This intervention of social work has been done in a public outpatient mental health center in the Madrid region. The methodology tries to put a voice to the individual patient testimonials through written texts. In these texts, experiences and stories, «their stories», are recovered and transmitted from various and particular ways of expression. Experiences that enhance not only the recovery of self-image and identity, but the relationship and representation of mental illness in society.
Keywords: social group work experience; severe and chronic mental illness; psychosocial rehabilitation; continuity of care; personal testimonies